Metagenomic evidence of suppressed methanogenic pathways along soil profile after wetland conversion to cropland - Wang, Nannan; Zhu, Xinhao; Zuo, Yunjiang; Liu, Jianzhao; Yuan, Fenghui; Guo, Ziyu; Zhang, Lihua; Sun, Ying; Gong, Chao; Song, Changchun; Xu, Xiaofeng (Frontiers in Microbiology, 2022)
Wetland conversion to cropland substantially suppresses methane (CH4) emissions due to the strong suppression of methanogenesis, which consists of various pathways. In this study, we evaluated the cultivation impacts on four predominant CH4 production pathways, including acetate, carbon dioxide (CO2), methylamines, and methanol, in a wetland and cultivated cropland in northeastern China. The results showed significant suppression of CH4 production potential and the abundance of genes for all four methanogenic pathways in cropland. The consistency between CH4 production and methanogenesis genes indicates the robustness of genomic genes in analyzing methanogenesis. The suppression effects varied across seasons and along soil profiles, most evident in spring and 0 – 30 cm layers. The acetate pathway accounted for 55% in wetland versus 70% in the cropland of all functional genes for CH4 production; while the other three pathways were stronger in response to cultivation, which presented as stronger suppressions in both abundance of functional genes (declines are 52% of CO2 pathway, 68% of methanol pathway and 62% of methylamines pathway, versus 19% of acetate pathway) and their percentages in four pathways (from 20% to 15% for CO2, 15% to 9% for methylamines and 10% to 6% for methanol pathway versus 55% to 70% for acetate pathway). The structural equation models showed that substrate availability was most correlated with CH4 production potential in the wetland, while the positive correlations of acetate, CO2, and methylamine pathways with CH4 production potential were significant in the cropland. The quantitative responses of four CH4 production pathways to land conversion reported in this study provide benchmark information for validating the CH4 model in simulating CH4 cycling under the land use and land cover change.